Organic carbon budget for the eastern boundary of the North Atlantic subtropical gyre: Major role of DOC in mesopelagic respiration - Santana Falcon, Yeray; Álvarez Salgado, X. Antón; Pérez-Hernández, M.Dolores; Hernandez-Guerra, Alonso; Mason, Evan; Aristegui, Javier (Scientific Reports, 2017)
Transports of suspended particulate (POCsusp) and dissolved (DOC) organic carbon are inferred from a box-model covering the eastern boundary of the North Atlantic subtropical gyre. Corresponding net respiration rates (R) are obtained from a net organic carbon budget that is based on the transport estimates, and includes both vertical and lateral fluxes. The overall R in the mesopelagic layer (100-1500 m) is 1.6 ± 0.4 mmol C m-2 d-1. DOC accounts for up to 53% of R as a result of drawdown of organic carbon within Eastern North Atlantic Central Water (ENACW) that is entrained into sinking Mediterranean Overflow Water (MOW) that leads to formation of Mediterranean water (MW) at intermediate depths (~900 m).